Strategic Group Dynamics - Mascarenhas, Briance (Academy of Management Journal, 1989)
A longitudinal study was conducted of strategic group dynamics over periods of economic stability, growth, and decline in international offshore oil-drilling. Some changes in group strategy were observed during economic growth and decline. Mobility rates among groups were observed to be higher during economic decline than during stability or growth; mobility was also higher between similar groups than between dissimilar groups. The number of groups remained to a large extent the same for an extended period, with the formation of only one additional group. The conditions leading to the formation of this new group are documented.